Pengembangan Batik Cikadu Tanjung Lesung Dengan Digital Marketing Menggunakan Digital Marketplace & Ecommerce Sebagai Bentuk Promosi - Dwi Fitrianingsih; Sucihati Sucihati; Fidziah Fidziah; Desty E Subroto (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2022)
The implementation of this community service conveys knowledge and skills in optimizing digital marketing by using a digital marketplace and E Commerce as a form of promotion at the Tourism Village of the Cikadu batik center, Tanjungjaya Village, Tanjung Lesung, Pandeglang, Banten Province. This Community Service activity is carried out by 132 lecturers who are members of the Indonesian Lecturer Association (IDRI) Banten Province, initiated to solve various problems that exist in the Cikadu Batik Studio Tanjung Lesung, specifically promotion or marketing issues. In the extension material, an explanation was given about the importance of promotion through Digital Marketing in order to increase sales value, business turnover and the added value of Cikadu Batik Products.